Benevolence as a Determining Factor in the Social Regulation of Internal and External Stakeholders: The Case of an Organization Aiming to Include Immigrants: Fostering Inclusivity through Benevolence - Lazzari-Dodeler, Nadia; Albert, Marie-Noëlle; Houle, Caroline (Revue Interventions économiques / Papers in Political Economy)

(untitled) (Association d’Économie Politique, 2025)
In this article, we examine the regulation of internal and external stakeholders within an organization seeking to promote the inclusion of immigrants. The method employed is autopraxeography , an approach grounded in the experiences of the co-researchers, who are also the authors of this article. This case highlights benevolence as a value that spreads and guides the daily actions of internal and external stakeholders through internalized norms. The dissemination of ethical values requires both instrumental and normative forms of regulation, as well as managerial legitimacy, which constitutes one of the main contributions of this study.